Can EGFR-Tyrosine Kinase Inhibitors (TKI) Alone Without Talc Pleurodesis Prevent Recurrence of Malignant Pleural Effusion (MPE) in Lung Adenocarcinoma - Verma, Akash; Chopra, Akhil; W. Lee, Yeo; D. Bharwani, Lavina; B. Asmat, Atasha; B.A Aneez, Dokeu; A. Akbar, Fazuludeen; Y.H. Lim, Albert; H. Chotirmall, Sanjay; Abisheganaden, John (Current Drug Discovery Technologies, 2016)
Background and objective: Epidermal Growth Factor Receptor-Tyrosine Kinase Inhibitors (EGFR-TKIs) are effective against lung adenocarcinoma. However, limited data is available assessing the effectiveness of EGFR-TKI use in preventing re-accumulation of MPE. To our knowledge, there is no literature on comparison of talc pleurodesis with EGFR-TKIs alone on re-accumulation of MPE in Asian population. We investigated if EGFR-TKI therapy for advanced lung adenocarcinoma with malignant pleural effusion (MPE) is also successful in preventing pleural fluid re-accumulation following initial drainage. Methods: An observational cohort study of patients with lung adenocarcinoma and MPE in the year 2012 was conducted. Results: 70 patients presented with MPE from lung adenocarcinoma. Fifty six underwent EGFR mutation testing of which 39 (69.6%) had activating EGFR mutation and 34 (87.1%) received TKI. 20 were managed by pleural fluid drainage only whereas 14 underwent talc pleurodesis following pleural fluid drainage. Time taken for the pleural effusion to re-accumulate in those with and without pleurodesis was 9.9 vs. 11.7 months, p=0.59 respectively. More patients (n=10, 25.6%) with activating EGFR mutation presented with complete opacification (white-out) of the hemithorax compared to none without activating EGFR mutation (p=0.02). Conclusion: In TKI eligible patients, early talc pleurodesis may not confer additional benefit in preventing re-accumulation of pleural effusion and may be reserved for non-adenocarcinoma histology, or EGFR negative adenocarcinoma. Complete opacification of the hemithorax on presentation may serve as an early radiographic signal of positive EGFR mutation status.
Keywords: pleural effusion